2010
DOI: 10.1088/1748-6041/5/4/045009
|View full text |Cite
|
Sign up to set email alerts
|

Study on poly(l-lactide -co- trimethylene carbonate): synthesis and cell compatibility of electrospun film

Abstract: The biomedical applications of poly(l-lactide) (PLLA) were limited by its high crystallinity. In this paper, the copolymerization of trimethylene carbonate (TMC) and l-lactide (LLA) was carried out to improve the flexibility of PLLA. The effects of feeding dose, reaction temperature and polymerization time were investigated, and the copolymers were characterized with (1)H nuclear magnetic resonance, Fourier transform infrared reflection, gel permeation chromatography differential scanning calorimetry, thermogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 20 publications
2
31
0
Order By: Relevance
“…Compared with plain polylactide (PLA), the acidity of degradation products -particularly detrimental in poorly vascularized implant sites -is reduced. Furthermore, the in vitro cytocompatibility of PLA-co-TMC was found to be significantly higher than that of PLA (32,33).…”
Section: Scaffold Fabricationmentioning
confidence: 89%
“…Compared with plain polylactide (PLA), the acidity of degradation products -particularly detrimental in poorly vascularized implant sites -is reduced. Furthermore, the in vitro cytocompatibility of PLA-co-TMC was found to be significantly higher than that of PLA (32,33).…”
Section: Scaffold Fabricationmentioning
confidence: 89%
“…The most notable feature from Figure 1A is that the M n decreases with the increased loading of the PC monomer, similarly observed by Gu et al in a recent study. 31 Interestingly, the mol% incorporation of PC in the copolymer, shown in Figure 1B, is consistently lower than the mol% PC loading. Both of these observations can be attributed to the faster rate of polymerization of LLA compared with that of PC as previously reported for similar TMC-LLA copolymers.…”
Section: Resultsmentioning
confidence: 88%
“…This will allow for improved mechanical properties to be observed under physiological conditions and in turn, helping to raise flexural strength of future composites in vivo . 31,41 To demonstrate the impact on the T g of the copolymer by the introduction of PC into PLLA, DSC traces of three polymers with different mol% incorporation of PC were obtained and compared (Figure 3). It is clearly observed that the T g decreases with the increased PC content.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the degradation kinetics and water ingestion depend on the degree of crystallinity of the polymers. Amorphous structure facilitates water molecular as well as some small molecular weight oligomers to enter into the polymer and access to the substance, while crystal structure inhibits the process [24,25]. Because of their highly crystalline structure, the in vivo hydrolysis process of PLLA/TMC and PLLA polymers are quite slow.…”
Section: Discussionmentioning
confidence: 99%